Probing the HIV-1 genomic RNA trafficking pathway and dimerization by genetic recombination and single virion analyses. - Michael D Moore; Olga A Nikolaitchik; Jianbo Chen; Marie-Louise Hammarskjöld; David Rekosh; Wei-Shau Hu (PLoS Pathogens)
Once transcribed, the nascent full-length RNA of HIV-1 must travel to the appropriate host cell sites to be translated or to find a partner RNA for copackaging to form newly generated viruses. In this report, we sought to delineate the location where HIV-1 RNA initiates dimerization and the influence of the RNA transport pathway used by the virus on downstream events essential to viral replication. Using a cell-fusion-dependent recombination assay, we demonstrate that the two RNAs destined for copackaging into the same virion select each other mostly within the cytoplasm. Moreover, by manipulating the RNA export element in the viral genome, we show that the export pathway taken is important for the ability of RNA molecules derived from two viruses to interact and be copackaged. These results further illustrate that at the point of dimerization the two main cellular export pathways are partially distinct. Lastly, by providing Gag in trans, we have demonstrated that Gag is able to package RNA from either export pathway, irrespective of the transport pathway used by the gag mRNA. These findings provide unique insights into the process of RNA export in general, and more specifically, of HIV-1 genomic RNA trafficking.